Writing through Loss: The Rise of Grief Narratives through the Lens of Linville's Self-complexity Theory. Issue 3 (3rd July 2019) - Meekings, Sam
ABSTRACT: Grief unmakes the self. Linville's social-cognitive theory [1985. "Self-complexity and Affective Extremity: Don't Put All of Your Eggs in One Cognitive Basket." Social Cognition 3: 94–120] suggests that our self-concept is reliant on the self's aspects, such as its roles. When one role (such as that of spouse or parent) is lost, the self-concept is forced to adapt. The application of Linville's self-complexity theory to recent autobiographical writing about loss sheds light on the strategies such texts use to deconstruct the self-concept and its differentiated aspects. This paper will examine recent grief memoirs by Joan Didion, Joyce Carol Oates, and Sandra M. Gilbert, as well as contemporary autofiction dealing with bereavement such as Karl Ove Knausgård's A Death in the Family [2013. Translated by Don Bartlett. London: Vintage], in order to analyse how such works renegotiate the self's aspects. It will also demonstrate what self-complexity theory can reveal about the intertextuality of these literary works, framing the quotation, referencing, literary discussion and heteroglossia that feature in all these narratives as a facet of self-aspects re-situating themselves within a world both familiar and suddenly changed. Finally, the paper will use Linville's theory to consider how loss complicates the (textual) self, and how narratives depicting such loss and its effects thus performs this complication.